استراتيجيات تعافي السياحة الإسلامية في ماليزيا خلال جائحة كوفيد 19: Islamic Tourism Recovery Strategies in Malaysia During the Covid-19 Pandemic - فاطمة الزهرة بن زيدان (Journal of North African Economies, 2025)
Malaysia has all the characteristics that make it an ideal Islamic tourist destination that ade-quately meets the requirements of Muslim tourists, which made it ranked first globally in the World Islamic Travel Index during the period (2019-2022) despite the negative impact of Covid 19 on the tourism sector. This study aims to analyze the effects of Covid 19 on Islamic tourism in Malaysia and the strategy it has followed to recover and revive the Islamic tourism sector during this pandemic. The results of the study indicate that Islamic tourism in Malaysia was significantly affected by Covid 19, and this is through a decrease in international passenger capacity by 85% and the can-cellation of 170.085 hotel rooms, which made the tourism and hotel industry sector lose more than 80% of its business